Pembelajaran Bahasa Arab Berbasis Teknologi Digital dan Implikasinya Terhadap Penguatan Literasi Keislaman di Era Digital Global - Satriawan Satriawan (Jurnal Al-Hibru, 2026)
The main problem faced is the tendency for digital technology to be used instrumentally and partially, with a greater emphasis on improving linguistic skills, while the role of Arabic as an epistemological medium for understanding Islamic teachings from their original sources has not been optimally utilized. This research employs a library research method, which is conceptual-theoretical in nature, utilizing a critical analysis approach and theoretical synthesis. Data is analyzed thru content analysis techniques and thematic analysis of various relevant scientific literature. The study results indicate that digital technology-based Arabic language learning has strategic potential in addressing the challenges of Islamic education in the global digital era, particularly in expanding access to Arabic-language Islamic sources, deepening understanding of religious texts, and developing students' digital critical literacy.The implications of this learning are multidimensional, encompassing cognitive, affective, and ethical aspects, which can only be optimally realized if learning is designed integratively by linking linguistic competence, contextual understanding of Islamic texts, and digital critical literacy into a single pedagogical unit. Keywords: Arabic language learning, digital technology, Islamic literacy.